1989
DOI: 10.1002/em.2850130407
|View full text |Cite
|
Sign up to set email alerts
|

Increased chromosome fragility as a consequence of blood folate levels, smoking status, and coffee consumption

Abstract: Chromosome fragility in 96 h, low-folate cultures was found to be associated with smoking status, coffee consumption, and blood folate level. The higher proportion of cells with chromosome aberrations in cigarette smokers was attributable to lower red cell folate levels in smokers compared with nonsmokers. There was a positive linear relationship between the average cups of coffee consumed per day and the proportion of cells with aberrations. This association was independent of the effects of smoking and red c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Folate is required for methylation of dUMP to dTMP (1). Under folate deficiency, the excess of dUMP leads to uracil misincorporation into DNA; repair of two nearby opposing lesions can cause a double-strand break (10,11). Highly proliferative cells such as mitogen-activated T lymphocytes are likely to have more uracil misincorporation, and thus more DNA double-strand breaks, when cultured in folate-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Folate is required for methylation of dUMP to dTMP (1). Under folate deficiency, the excess of dUMP leads to uracil misincorporation into DNA; repair of two nearby opposing lesions can cause a double-strand break (10,11). Highly proliferative cells such as mitogen-activated T lymphocytes are likely to have more uracil misincorporation, and thus more DNA double-strand breaks, when cultured in folate-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…MacGregor et al (8) reported that folate deficiency causes cytogenetic damage in mice and that caffeine acts synergistically with inadequate folate status to augment this damage. Additionally, consumption of coffee and tea has been directly related to chromosome fragility (9) and chromosomal damage (10) in peripheral lymphocytes and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…After treatment with a daily oral dose of 15-20 ng/mg (higher than the normal doses) for 25 days, the frequency of micronuclei in this patient was stabilized (Everson et al, 1988). Another study on smokers and non-smokers showed a significant relationship between smoking and low levels of folate in the blood, which causes chromosomal fragility and leads to aberrations (Chen et al, 1989).…”
Section: Epidemiological Evidencementioning
confidence: 75%
“…Blood from the same individuals was analysed for uracil content (Everson et al, 1988;Chen et al, 1989) and was found that the rate of uracil misincorporation had a 70-fold increase in people whose serum folate was lower than 4 ng/ml compared with people whose serum folate was above 4 ng/ml (Blount et al, 1997).…”
Section: Epidemiological Evidencementioning
confidence: 99%